Sosialisasi Penggunaan Wordwall Sebagai Media Pembelajaran Digital kepada Guru di UPTD SDN Purwamekar - Hafiziani Eka Putri; Eva Firdausy Solihah; Rizky Purwatresna Senjaya; Abriani Larassati; Ajeng Putri Wulandari Yuwono; Hillary Ester Hutasoit (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Technology is one of the important things in various fields, especially in the field of education, in the technological age like now a professional educator must be able to keep up with the times. One of them is by making digital-based learning media, the application of learning using digital media can make it easier for students to receive learning in a fun way. So it is necessary to have a workshop for teachers in making digital-based learning media using a website called wordwall at UPTD SDN Purwamekar. This service in the form of a workshop shared with educators at UPTD SDN Purwamekar how to apply the creation of digital learning media on the wordwall website. Based on the results of the questionnaire given, 80% of the participants who attended did not know this wordwall website, and 20% already knew but had never used it. As a result of this workshop, the participants who attended came to understand and were able to apply wordwalls to learning activities.